Deteksi Dini Peripheral Artery Disease (PAD) dengan Risiko Diabetes Mellitus melalui Skrining Ankle Brachial Index (ABI) - Evodius Nasus; Ekawati Saputri; Bangu Bangu; A. Musdalifah; Fena Wulandari; Nurul Fajri (Institut Nalanda, 2026)
Peripheral artery disease (PAD) is a common vascular complication in individuals with diabetes mellitus and hypertension and may lead to diabetic foot ulcers and limb amputation if not detected early. This community service program aimed to conduct early detection of PAD among high-risk populations through Ankle Brachial Index (ABI) screening and Random Blood Glucose (RBG) testing. The activity was carried out in Sabiano Village, Wundulako Subdistrict, Kolaka Regency, involving 27 participants aged 42–72 years. The methods included measuring systolic blood pressure in the arm and ankle using the MESI ABPI MD device to determine ABI values and assessing RBG levels to identify hyperglycemia. The results showed that most participants had normal ABI values ranging from 0.90 to 1.30. However, one participant had an ABI value below 0.90, indicating a risk of PAD, while five participants had RBG levels of ≥200 mg/dL, suggesting uncontrolled blood glucose levels. These findings indicate the presence of individuals requiring further medical evaluation and follow-up. ABI screening proved to be an effective, practical, and non-invasive method for identifying vascular disorders in at-risk populations. This program highlights the importance of routine screening as a preventive effort to reduce vascular complications and strengthen primary healthcare services through early detection and timely intervention.